Does Diversification Improve the Performance of German Banks? Evidence from Individual Bank Loan Portfolios - Evelyn Hayden; Daniel Porath; Natalja von Westernhagen (Oesterreichische Nationalbank (OeNB), 2006)
Should banks be diversified or focused? Does diversification indeed lead to increased performance and therefore greater safety on the part of banks as traditional portfolio and banking theory would suggest? This paper investigates the link between banks' profitability and their portfolio diversification across different industries, broader economic sectors and geographical regions. To explore this issue, we use a unique data set of the individual bank loan portfolios of 983 German banks for the period from 1996 to 2002. The overall evidence we provide shows that there are no large performance benefits associated with diversification since each type of diversification tends to reduce the banks' returns. Additionally, we find that banks do not use diversification to operate at a constant level of risk-return efficiency, which implies that banks are not risk-return efficient. Moreover, we find that the impact of diversification strongly depends on the risk level. However, only for moderate risk levels and in the case of industrial diversification does diversification significantly improve the banks' returns.
Keywords: G21; G28; G32; 330; focus; diversification; monitoring; bank returns; bank risk